Pengembangan EModul Pendidikan Multikultural Berbasis Pendekatan Aditif Untuk Siswa Sekolah Dasar - Muh Muhaimin; Hamidaturrohmah; Nur Afif Wahyudin; Natasya Arieni Fasya (Jurnal Elementaria Edukasia, 2023)
The existence of a lot of diversity in elementary schools makes it important to instill non-discrimination, mutual respect and tolerance in students so that inclusiveness can be realized. This research aims to develop an additive-based multicultural education module as teaching material for global diversity character education and noble character for elementary school students. This research method is development research by adopting the Plomp stage which includes the initial investigation, planning (design), and realization stages, test stages, evaluation and revision. Data analysis includes 3 stages, namely data condensation, data presentation, conclusion drawing /verification). The eligibility data of the e module was obtained from expert validation and teacher response questionnaires. The outcome of this research is the creation of a digital teaching material that can effectively teach diversity from a global perspective. The e-module will be enriched with images, videos, audios, and interactive elements to enable students to gain a profound understanding of diverse cultures. By utilizing this module, students' awareness of cultural diversity will be heightened, and it will promote an inclusive attitude. Students will learn to value cultural differences and respect diverse values. The e-module will provide students with opportunities to interact with multicultural content, share their viewpoints, and communicate with students from different cultures through an online platform.